(untitled) (The International Journal for Scientific Research, 2024)
The study aims to demonstrate the impact of digital transformation in developing the performance of individuals working in the Education and Training Evaluation Commission in the Kingdom of Saudi Arabia, in a way that ensures the proper application of this modern digital technology, which helps improve operational efficiency within all departments and departments of the Education and Training Evaluation Commission, and from the results using the descriptive approach, the management used The questionnaire for a sample of 100 workers that the study found is that there is a positive impact on some dimensions of digital transformation: 1- There is a deficiency in the digital transformation process in the Education and Training Evaluation Authority and a weakness in the institutional structure necessary for the digital transformation process in the Education and Training Evaluation Authority. 2- There is a desire among the working cadres The company has to carry out digital transformation to facilitate business and help speed up the completion of tasks. Among the most important recommendations and proposals that the study concluded are the following: 1- The most important recommendation is to give employees with digital talent freedom of action as well as the ability to implement the necessary changes. The company should remain open in accepting failures as digital talents are created and experimented with. Digital talent prefers to work in an environment with a culture that allows and encourages creative thinking and flexibility. 2- Management should be developed within the company in which employees take the initiative in learning and developing their digital capabilities and are rewarded accordingly. This will motivate employees to develop their digital skills. A system of monetary and non-monetary incentives must be created for employees who proactively acquire the digital capabilities needed by the authority.